Identification and Quantification of a Phytotoxic Metabolite from Alternaria dauci - Leyte-Lugo, Martha; Richomme, Pascal; Poupard, Pascal; Peña-Rodriguez, Luis M. (Molecules (Basel, Switzerland), 2020)
Alternaria dauci is the causal agent of Alternaria leaf blight (ALB) in carrot (Daucus carota) crops around the world. However, to date, A. dauci has received limited attention in its production of phytotoxic metabolites. In this investigation, the bioassay-guided isolation of the extract from liquid cultures of A. dauci resulted in the isolation of two metabolites identified as α-acetylorcinol (1) and p-hydroxybenzoic acid (2), based on their spectroscopic data and results from chemical correlation reactions. Testing of both metabolites in different assays showed an important phytotoxic activity for p-hydroxybenzoic acid (2) when tested in the leaf-spot assay on parsley (Petroselinum crispum), in the leaf infiltration assay on tobacco (Nicotiana alata) and marigold (Tagetes erecta), and in the immersion assay on parsley and parsnip (Pastinaca sativa) leaves. Quantification of the two metabolites in the crude extract of A. dauci kept at different times showed that p-hydroxybenzoic acid (2) is one of the first metabolites to be synthesized by the pathogen, suggesting that this salicylic acid derivative could play an important role in the pathogenicity of the fungus.